A standardizable human-based psoriasis skin model for drug development - Glasebach, Hanna; Rupp, Steffen; Burger-Kentischer, Anke (Frontiers in Medicine, 2025)
Psoriasis is a chronic inflammatory autoimmune disease with a prevalence of 2–3% in the western population. For the development of urgently needed new therapeutic options, standardizable and human-relevant disease models are essential. The transcription factor signal transducer and activator of transcription 3 (STAT3) plays a key role in the pro-inflammatory response of psoriatic keratinocytes. In this study, we established STAT3 overexpressing human keratinocytes and combined the cells with our epidermis and immune cell supplemented full-thickness skin model to generate a novel in vitro psoriasis model. In the full-thickness skin models STAT3 overexpression by its own was sufficient to induce enhanced expression of the psoriasis marker S100A7. Both epidermal and full-thickness skin models set up from STAT3 overexpressing keratinocytes showed a stronger psoriasis-like phenotype upon pro-inflammatory stimuli such as treatment with cytokines or integration of T cells compared to skin models set-up from the wild-type keratinocyte cell line. Thus, the STAT3 overexpression in keratinocytes induced a pre-psoriatic like phenotype in untreated skin models and enhanced the sensitivity of the skin models to psoriatic stimuli. This reflects the genetic susceptibility in psoriasis patients, which is responsible for the differences between non-lesional skin in patients and healthy skin. The novel STAT3 overexpressing in vitro skin model mimics many psoriatic hallmarks, is based on well-established immortalized primary keratinocytes and highly reproducible. Therefore, we expect it to be a well-suited psoriasis model for drug screening and validation approaches in a preclinical setting.